2020
DOI: 10.1371/journal.pone.0240329
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of severe pneumonia by hinokitiol in a murine antimicrobial-resistant pneumococcal pneumonia model

Abstract: Streptococcus pneumoniae is often isolated from patients with community-acquired pneumonia. Antibiotics are the primary line of treatment for pneumococcal pneumonia; however, rising antimicrobial resistance is becoming more prevalent. Hinokitiol, which is isolated from trees in the cypress family, has been demonstrated to exert antibacterial activity against S . pneumoniae in vitro regardless of antimicrobial resistance. In this study, the efficacy of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Following the administration of anesthesia (a mixture of medetomidine hydrochloride [Orion Corporation, Espoo, Finland], midazolam [Sandoz, Tokyo, Japan], and butorphanol [Meiji Seika Pharma Co., Ltd.]), BALB/c mice were intratracheally infected with S. pneumoniae strain NU4471 (5.0 × 10 8 CFU in 50 μl PBS) using a MicroSprayer aerosolizer (Penn-Century, Inc., Philadelphia, PA, USA) as described previously ( 53 ). CLR or ERY powder was dissolved in 5% gum arabic solution.…”
Section: Methodsmentioning
confidence: 99%
“…Following the administration of anesthesia (a mixture of medetomidine hydrochloride [Orion Corporation, Espoo, Finland], midazolam [Sandoz, Tokyo, Japan], and butorphanol [Meiji Seika Pharma Co., Ltd.]), BALB/c mice were intratracheally infected with S. pneumoniae strain NU4471 (5.0 × 10 8 CFU in 50 μl PBS) using a MicroSprayer aerosolizer (Penn-Century, Inc., Philadelphia, PA, USA) as described previously ( 53 ). CLR or ERY powder was dissolved in 5% gum arabic solution.…”
Section: Methodsmentioning
confidence: 99%
“…Considering S. pyogenes (A458) genetic similarity to S. pneumoniae and S. pyogenes (SSI-9), it was found that hinokitiol may have antibacterial effects according to previous studies [4,6]. Therefore, there is reason to believe that hinokitiol affects S. pyogenes (A458) as well.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, there is reason to believe that hinokitiol affects S. pyogenes (A458) as well. Hinokitiol has shown to have strong antibacterial effects, making it a suitable candidate [4,6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations